Rural youth and educational processes (Research, Society and Development, 2020)
This work had as aim to reflect on the social condition of rural youth and to point out dynamic aspects of emancipatory educational processes, focusing on young people from rural settlements in the region of Paraíba called Brejo. The academic and social relevance of this work is given in the understanding of the social condition reality of rural youth from its envolvement with these processes, contributing to studies in the educational field. The qualitative research approach allowed us to adopt the following procedures for fieldwork: bibliographical survey and review, participant observation and interviews (semi-structured script). As a result, we present a reflection on rural youth as social category and  subject of transformation and we highlight the relation between educational processes and the principles of a liberating education turned to realization. We consider that these processes articulate and mobilize the participation of this youth in public spaces, allowing insertions and practices for the young subject autonomy and for the formation of rural youth identity.